The Communication Strategies Relationship of Non-Native Speakers with Extra Linguistics Factors in Target Language: A Case Study - ., Mohd Helmi Pangat (International Journal of Advanced Science and Technology, 2019)
The study was administered to find the types and frequency of communication strategies used by students of various levels (excellent, moderate and weak) in second language expression. Besides, this study also analyzed the extent to which extra linguistics influenced non-native speaker communication strategies. This study considered oral error as a communication strategy that could benefit non-native speakers. Therefore, the researcher conducted a study at a school called SRJKC Onn Pong 2. A total of 30 students of different competency levels (ten excellent, ten moderate and ten weak) from standard five batches were involved in this study. The findings showed that all levels of students used the non-verbal communication strategy (SKBBL) as much as 173 cases in comparison with 96-language oral communication strategy (SKBL). The types and frequency of communication strategies vary by student level. A total of 269 cases were used by excellent students (77 cases), moderate students (82 cases), and primary students used the most communication strategies, which were 110 cases. Also, the findings of the analysis indicate that the extra-linguistic for non-native speakers play an important role in determining the type and frequency of communication strategies that should be used during speech with interlocutors.